6
$\begingroup$

This was buried in a rather long question, so I'm asking it separately to give it some air. Define, $$A_3={_3F_2}\left(1,\frac{\color{blue}1}2,\frac22;\ \frac43,\frac53;\ \frac4{27}\right)$$ $$B_3={_3F_2}\left(1,\frac{\color{blue}2}2,\frac32;\ \frac43,\frac53;\ \frac4{27}\right)$$ $$C_3={_3F_2}\left(1,\frac{\color{blue}3}2,\frac42;\ \frac43,\frac53;\ \frac4{27}\right)$$

These generalized hypergeometric functions belong to infinite families that differ in the starting numerator (in blue). Given the three roots $x_n$ of $x^3-x+1=0$. Then,

$$\frac12 A_3= \int_1^\infty \frac{-3+2x}{x^3-x+1}dx =-\sum_{n=1}^3 x_n\ln(1-x_n)=0.517977\dots$$

$$\frac13 B_3 = \int_1^\infty\frac1{x(x^3-x+1)}dx=-\sum_{n=1}^3 \frac{\ln(1-x_n)}{-3+2x_n}=0.371216\dots$$

Q: But what is $\displaystyle C_3 = 3\sum_{n=1}^\infty\frac1{\binom{3n}n}$ as a similar integral?

$\color{green}{Update:}$

Courtesy of David H's answer, by generalizing we find, $$k\sum_{n=1}^\infty\frac1{\binom{kn}n}=\int_1^\infty\frac1{(x^k-x+1)^2}dx$$ hence, $$C_3 = \int_1^\infty\frac1{(x^3-x+1)^2}dx=\tfrac{12}{23}-\tfrac{6}{23}\sum_{n=1}^3 \frac{3x_n + x_n^2}{-3+2x_n}\,\ln(1-x_n)=1.242966\dots$$

and a closed-form using the roots $x_n$.

$\endgroup$
6
$\begingroup$

Recall that the beta function may be defined via the integral representation

$$\operatorname{B}{\left(z,w\right)}:=\int_{0}^{1}t^{z-1}\left(1-t\right)^{w-1}\,\mathrm{d}t;~~~\small{\Re{\left(z\right)}>0\land\Re{\left(w\right)}>0}.$$

Using the infinite series definition of the generalized hypergeometric function, we find

$$\begin{align} C_{3} &={_3F_2}{\left(1,\frac32,2;\frac43,\frac53;\frac{4}{27}\right)}\\ &=\sum_{k=0}^{\infty}\frac{\left(1\right)_{k}\,\left(\frac32\right)_{k}\,\left(2\right)_{k}\,\left(\frac{4}{27}\right)^{k}}{\left(\frac43\right)_{k}\,\left(\frac53\right)_{k}\,k!}\\ &=\sum_{k=0}^{\infty}\frac{2\,\Gamma{\left(k+2\right)}\,\Gamma{\left(2k+2\right)}}{\Gamma{\left(3k+3\right)}}\\ &=\sum_{n=1}^{\infty}\frac{2\,\Gamma{\left(n+1\right)}\,\Gamma{\left(2n\right)}}{\Gamma{\left(3n\right)}}\\ &=\sum_{n=1}^{\infty}\frac{2n\,\Gamma{\left(n\right)}\,\Gamma{\left(2n\right)}}{\Gamma{\left(3n\right)}}\\ &=2\sum_{n=1}^{\infty}n\,\operatorname{B}{\left(n,2n\right)}\\ &=2\sum_{n=1}^{\infty}n\int_{0}^{1}\mathrm{d}t\,t^{n-1}\left(1-t\right)^{2n-1}\\ &=2\int_{0}^{1}\mathrm{d}t\,\sum_{n=1}^{\infty}nt^{n-1}\left(1-t\right)^{2n-1}\\ &=2\int_{0}^{1}\frac{\mathrm{d}t}{t\left(1-t\right)}\sum_{n=1}^{\infty}n\left[t\left(1-t\right)^{2}\right]^{n}.\\ \end{align}$$

Then, using the infinite series,

$$\sum_{n=1}^{\infty}nz^{n}=\frac{z}{\left(1-z\right)^{2}};~~~\small{\left|z\right|<1},$$

we obtain the integral form for $C_{3}$

$$\begin{align} C_{3} &=2\int_{0}^{1}\frac{\mathrm{d}t}{t\left(1-t\right)}\cdot\frac{t\left(1-t\right)^{2}}{\left[1-t\left(1-t\right)^{2}\right]^{2}}\\ &=2\int_{0}^{1}\mathrm{d}t\,\frac{\left(1-t\right)}{\left[1-t\left(1-t\right)^{2}\right]^{2}}\\ &=2\int_{0}^{1}\mathrm{d}u\,\frac{u}{\left[1-\left(1-u\right)u^{2}\right]^{2}};~~~\small{\left[1-t=u\right]}\\ &=\int_{0}^{1}\mathrm{d}u\,\frac{2u}{\left(1-u^{2}+u^{3}\right)^{2}}.\blacksquare\\ \end{align}$$

$\endgroup$
  • 2
    $\begingroup$ Great! I'm glad I made this side-question. I knew there had to be a way to express it using the roots $x_n$ as well. $\endgroup$ – Tito Piezas III Jan 10 '17 at 12:30

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.